Multi-Level Influences on Center-Pivot Irrigation Adoption in Alabama - Price, Ashleigh N.; Pathak, Ruchie; Guthrie, Gregory M.; Kumar, Mukesh; Moftakhari, Hamed; Moradkhani, Hamid; Nadolnyak, Denis; Magliocca, Nicholas R. (Frontiers in Sustainable Food Systems, 2022)
Rates of poverty and economic inequality in rural Alabama are among the nation’s highest and increasing agricultural productivity can provide a needed boost to these communities. The transition from rain-fed to irrigation-fed (RFtoIF) agriculture has significantly increased farm productivity and profitability elsewhere in the United States. Despite this potential to enhance stability and resilience in rural economies, irrigated cropland accounts for only 5% of Alabama’s total cropland as numerous barriers remain to irrigation adoption. To encourage RFtoIF transition, it is imperative to identify the challenges faced by individual farmers at farm, community, and state levels. This study presents a multi-level mixed effects survival analysis to identify the physiographic, socioecological, and economic factors that influence the location and timing of irrigation adoption. We integrate spatiotemporal cropland and climatological data with field-verified locations of center-pivot irrigation systems, local physiographic characteristics, and parcel-level surface water access and average well depth. Access to surface water, costs to access groundwater, and soil characteristics were generally important influences in all regions, but regions were differentiated by the extent to which new irrigation was more responsive to social influences versus precipitation and price trends. Our findings also highlighted the diversity of farming conditions across the state, which suggested that diverse policy tools are needed that acknowledge the varying motivations and constraints faced by Alabama’s farmers.